2015
DOI: 10.1111/eci.12505
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of RV isovolumic acceleration and tissue strain in moderate HFrEF

Abstract: our study demonstrated a useful prognostic role of RV strain and IVA, which are parameters of subclinical RV impairment. Patients with low values may benefit from a more aggressive therapy and a closer follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…X [20] Our study demonstrated a useful prognostic role of right ventricular (RV) strain and isovolumic acceleration, which are parameters of subclinical RV impairment. Patients with low values may benefit from a more aggressive therapy and a closer follow-up.…”
Section: [13]mentioning
confidence: 87%
See 1 more Smart Citation
“…X [20] Our study demonstrated a useful prognostic role of right ventricular (RV) strain and isovolumic acceleration, which are parameters of subclinical RV impairment. Patients with low values may benefit from a more aggressive therapy and a closer follow-up.…”
Section: [13]mentioning
confidence: 87%
“…Prognostic value of RV isovolumic acceleration and tissue strain in moderate HFrEF [20] (Edoardo Sciatti and Enrico Vizzardi)…”
mentioning
confidence: 99%
“…This parameter has the advantage of being a relatively load-independent index of global RV systolic performance that has proved to be useful in a variety of clinical settings, including acute pulmonary embolism [28], heart failure with reduced LVEF (as a marker of subclinical RV impairment [29]), as well as in patients after mitral valve surgery (as a more reliable measure of early recovery in RV contractility [30]). …”
Section: Myocardial Acceleration During Isovolumic Contractionmentioning
confidence: 99%
“… and Sciatti et al . were selected for the final round and the Council on the basis of quality, novelty and impact selected for the 2016 ESCI Award for Best Clinical Research Article the study by Caballero et al . entitled ‘Influence of aortic regurgitation after TAVI on left ventricular filling pattern’ .…”
mentioning
confidence: 99%
“…In November 2015, the Council of the European Society of Clinical Investigation (ESCI) evaluated all clinical research articles published in the European Journal of Clinical Investigation (EJCI) from November 2014 to October 2015. Six articles by Chung et al [1], Caballero et al [2], de Beus et al [3], Distelmaier et al [4], Deetman et al [5] and Sciatti et al [6] were selected for the final round and the Council on the basis of quality, novelty and impact selected for the 2016 ESCI Award for Best Clinical Research Article the study by Caballero et al entitled 'Influence of aortic regurgitation after TAVI on left ventricular filling pattern' [2].…”
mentioning
confidence: 99%